The Impact of Community Based Critical Land and Water Resources Management Program on Community Welfare (Case in Nagari Tanjuang Bonai, Lintau Buo, Tanah Datar, West Sumatera) - Suresman Riad; Yonariza Yonariza; Ifdal Ifdal (Universitas Andalas, 2019)
Community Based - Critical Land and Water Resources ManagementProgram is a program to handle critical land and poverty alleviation inIndonesia. The objective of this program is to improve the condition ofthe poor living surrounding critical land forests. Participatory approach isemployed in this program by involving multi-stakeholders to improvecritical land to become productive land in order to increase income andwelfare of the community. The purpose of this study was to analyze theimpact of Community Based - Critical Land and Water ResourcesManagement Program on community’s income who were directlyinvolved in managing the critical land. This study uses a case studyapproach with application of descriptive quantitative and qualitativemethod in data analysis. Nagari Tanjuang Bonai, Lintau Buo UtaraDistrict, Tanah Datar District, West Sumatra Province was purposivelyselected as research location. The respondents were 32 farmers who aremembers of Sago Lestari farmer group (Poktan) as program implementersfrom 2012 to 2016. The primary data were collected using questionnairesfrom farmers, while interview guide was used to obtain information fromkey informants. The results of this study indicate that the program hasbeen able to provide benefits to community in form of increasing infarmers’ income. The average income increases by 34.11% of the totalfarmers’ income participating in the program. This implies that theprogram has been able to improve the community’s welfare. It indirectlyreduces the area of critical land and change it into productive land.